Anti-fog coating for vehicle-mounted camera and preparation method of anti-fog coating
The anti-fog coating, composed of resin materials and modified composite particles in a specific ratio, solves the problems of image quality degradation and performance failure of vehicle cameras in foggy weather and high temperature and humidity environments, achieving high efficiency and durability in harsh weather conditions.
Patent Information
- Application Number
- CN202411400282.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The image quality of vehicle cameras deteriorates in adverse weather conditions such as fog, affecting the safety and reliability of autonomous driving systems. Existing anti-fog coatings are prone to moisture absorption and saturation in high temperature and high humidity environments, leading to performance failure.
An anti-fog coating composed of resin materials, methyl vinyl silicone rubber, microcapsules, moisture-controlling powder, and functional fillers in a specific ratio is formed by using modified composite particles and crosslinking aids to create a composite structure in which multiple titanium dioxide particles encapsulate the framework particles. This enhances the dispersion effect and mechanical properties, controls water molecule migration, and prevents moisture saturation.
This anti-fog coating maintains excellent anti-fog and mechanical properties in high-temperature and high-humidity environments, avoids moisture saturation, and ensures camera clarity and security. It is suitable for automotive cameras.
Abstract
Description
Technical Field
[0001] The present application relates to the field of paint coatings, and in particular to an anti-fog coating for a vehicle-mounted camera and a preparation method thereof. Background Art
[0002] With the rapid development of road traffic vehicles, especially new energy vehicles, trains and other motor vehicle industries in recent years, the development of vehicle-mounted cameras has shown a rapid trend in recent years. With the continuous advancement of unmanned driving technology, including the fully automatic operation technology of high-automation level train vehicles such as GoA3 and GoA4, vehicle-mounted cameras have become one of the key sensors; whether in rainy days, snowy days, foggy days or at night, road traffic vehicles, including unmanned cars and urban rail transit trains, will need to use anti-collision image sensors, speed sensors, pantograph monitoring and other advanced sensors with cameras and intelligent algorithms to perceive and analyze environmental information to make decisions to achieve better safe operating conditions. Therefore, these sensors are crucial for accurately detecting obstacles and road conditions for urban rail transit trains and unmanned vehicles, so that trains, cars and other vehicles can travel safely.
[0003] The impact of the fogging problem of on-board cameras on the vehicle's unmanned driving system and urban rail transit signal system is obvious. First, fogging will cause the camera image quality to deteriorate, limiting the unmanned driving system's ability to perceive environmental information such as roads, signs, obstacles, and the ability of the train's fully automatic operation system to monitor the trackside environmental information and the operation of train equipment, which may lead to misjudgment and delayed decision-making, increasing the risk of accidents. Secondly, object detection is a problem. After the camera fogs up, the edges and details cannot be clearly identified, affecting the object detection and recognition capabilities, thereby affecting the decision-making and obstacle avoidance capabilities of unmanned train vehicles or cars. Therefore, ensuring the cleanliness and normal working state of the on-board camera and adopting appropriate anti-fog measures are important means to ensure the safety and reliability of unmanned driving systems such as trains and cars. As a technical means that can effectively ensure the cleanliness of the on-board camera, the anti-fog coating of the on-board camera has received widespread attention in recent years. It can effectively achieve the sealing, humidity control and protection of the on-board camera, and effectively reduce the possibility of fogging inside and outside the camera to ensure the reliability and clarity of the camera.
[0004] The anti-fog coating for a vehicle-mounted camera provided in the present application not only has excellent anti-fog performance, but also ensures its good aging resistance, corrosion resistance and mechanical properties, and can ensure its performance stability in a long-term high temperature and high humidity environment, avoiding the moisture absorption and saturation phenomenon of existing anti-fog coatings in a long-term high temperature and high humidity environment, so that it ensures the anti-condensation effect under normal use, realizes the dynamic balance of the ambient humidity in the vehicle-mounted camera, and plays a role in protecting optical and electronic components within a suitable humidity range, and has very excellent application prospects. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present application provides an anti-fog coating for a vehicle-mounted camera. The raw materials are, by mass: 45 to 60 parts of resin material, 10 to 20 parts of methyl vinyl silicone rubber, 10 to 15 parts of microcapsules, 20 to 35 parts of moisture control powder, 15 to 25 parts of functional fillers, 5 to 10 parts of cross-linking monomers, 3 to 5 parts of cross-linking aids, 5 to 8 parts of foaming agents, 3 to 4 parts of antibacterial agents, 2 to 4 parts of UV resistant agents, 1 to 2 parts of initiators, 2 to 4 parts of catalysts, and 8 to 15 parts of additives.
[0006] As a preferred solution, the mass ratio of the resin material, methyl vinyl silicone rubber and cross-linking monomer is (46-55): (12-18): (5-8).
[0007] As a preferred solution, the mass ratio of the resin material, methyl vinyl silicone rubber and cross-linking monomer is (48-52): (14-15): (6-7).
[0008] As a preferred solution, the mass ratio of the microcapsules, the moisture control powder and the functional filler is (12-14): (22-28): (18-25).
[0009] As a preferred solution, the mass ratio of the microcapsules, the moisture control powder and the functional filler is (13-14): (24-26): (22-24).
[0010] As a preferred solution, the resin material is a composition of a hyperbranched polyurethane acrylate resin and a polyethylene glycol diacrylate resin.
[0011] As a preferred solution, the mass ratio of the hyperbranched polyurethane acrylate resin to the polyethylene glycol diacrylate resin is (4-4.5):(0.9-1.3).
[0012] As a preferred solution, the mass ratio of the hyperbranched polyurethane acrylate resin to the polyethylene glycol diacrylate resin is (4-4.2):(1-1.1).
[0013] As a preferred solution, the weight average molecular weight of the hyperbranched polyurethane acrylate resin is 10000-15000 Da.
[0014] As a preferred solution, the hyperbranched polyurethane acrylate resin.
[0015] As a preferred solution, the weight average molecular weight of the polyethylene glycol diacrylate resin is 600-1000 Da.
[0016] As a preferred solution, the viscosity of the methyl vinyl silicone rubber is 1000-1500 mPa·s at 25°C.
[0017] As a preferred solution, the microcapsule is paraffin-urea-formaldehyde resin microcapsule.
[0018] As a preferred solution, the moisture control powder is a composition of nano-alumina, nano-silica gel, calcium chloride, magnesium chloride and calcium nitrate.
[0019] As a preferred solution, the mass ratio of the nano-alumina, nano-silica gel, calcium chloride, magnesium chloride and calcium nitrate is (6-8): (4-4.5): (3-3.5): (1-2): (1-2).
[0020] As a preferred solution, the average particle size of the nano-alumina is 10-20 nm.
[0021] As a preferred solution, the specific surface area of the nano silica gel is 400-500m 2 / g.
[0022] As a preferred solution, the average particle size of the calcium chloride is 15-20 μm.
[0023] As a preferred solution, the average particle size of the magnesium chloride is 10-15 μm.
[0024] As a preferred solution, the average particle size of the calcium nitrate is 20-25 μm.
[0025] As a preferred solution, the functional filler is a composition of calcium carbonate and modified composite particles.
[0026] As a preferred solution, the mass ratio of the calcium carbonate to the modified composite particles is (3-4): (1.5-2.2).
[0027] As a preferred solution, the average particle size of the calcium carbonate is 200-300 nm.
[0028] As a preferred solution, the preparation method of the modified composite particles comprises the following steps: S1: adding aluminum chloride and titanium dioxide to DMF, ultrasonically dispersing at 200-250W for 20-30min, then adding citric acid, succinic anhydride and methacryloxysilane coupling agent, heating to 60-70°C for 2-3h, centrifugally filtering, washing and drying to obtain pre-treated mixed particles; S2: adding the pre-treated mixed particles to a mixed solvent of DMF and methanol, adding p-aminobenzoic acid and terephthalic acid, and evaporating in a dense The reaction vessel is sealed and stirred at 120-140°C and 200-240 rpm for 16-20 hours. After the reaction is completed, it is naturally cooled to room temperature, centrifuged and filtered, washed with DMF and methanol in a cycle for 2-3 times, and vacuum dried to obtain pre-product particles; S3: the pre-product particles and ethanol are added to deionized water, the pH is adjusted to 10-10.5 with ammonia water, tetraethyl orthosilicate and triethanolamine are added, the temperature is raised to 60-65°C and kept warm for 1-1.5 hours, and after completion, the deionized water is circulated and washed for 2-3 times, and vacuum dried to obtain the product.
[0029] As a preferred solution, the mass ratio of aluminum chloride, titanium dioxide, citric acid, succinic anhydride and methacryloxysilane coupling agent is (5-5.5): (0.6-1): (0.5-0.7): (2-2.2): (0.2-0.3).
[0030] As a preferred solution, the mass ratio of DMF to methanol in the mixed solvent of S2, DMF and methanol is (3~4):1.
[0031] As a preferred solution, in the pretreated mixed particles, the mass ratio of aminobenzoic acid to terephthalic acid is (3-3.2): (2.1-2.4): (0.5-0.8).
[0032] As a preferred solution, the mass ratio of the pre-product particles, tetraethyl orthosilicate and triethanolamine is (3.6-4): (0.4-0.6): (0.05-0.1).
[0033] As a preferred solution, the average particle size of the titanium dioxide is 5-10 nm.
[0034] As a preferred solution, the average particle size of the modified composite particles is 420-550 nm.
[0035] In the present application, the addition of the above-mentioned modified composite particles can effectively improve the high temperature resistance, corrosion resistance, and mechanical and other properties of the anti-fog coating, especially can maintain good performance stability in a high temperature and high humidity environment for a long time, and can continue to maintain excellent anti-condensation effect at room temperature. The modified composite particles prepared in the present application coordinate and embed titanium dioxide particles on the surface of the adsorbed framework particles, thereby forming a composite structure in which multiple titanium dioxide particles are coated with framework particles. The existence of this structure can first utilize the multiple active groups of the surface titanium dioxide to form good hydrogen bonds or intermolecular forces with the organic resin in the coating system to fix it, thereby achieving its good dispersion effect, reducing the pore size of the particle pores, providing a good support effect for the mechanical properties of the coating system, and ensuring a good working environment system for other functions.
[0036] Secondly, the formed composite structure can use the surface titanium dioxide as a good guiding carrier, which can serve as a good guiding carrier for water molecules at room temperature. When inside the coating, it can assist in absorbing the water molecules inside the coating. When on the surface, it can form a rough coating surface with continuous peak-valley structure while adsorbing water molecules, thereby greatly improving the surface energy of the coating, effectively enhancing the aggregation of water molecules on the coating surface, and increasing the probability of forming a hydrated layer on the coating surface.
[0037] Finally, the framework particles located at the center of the composite structure can desorb water molecules in a high temperature environment through the amino groups and their own adsorption characteristics, thereby maintaining a low moisture absorption level in a high temperature and high humidity environment. When the ambient temperature drops below the critical temperature, it can re-achieve excellent water molecule adsorption, thereby avoiding the moisture saturation phenomenon of the existing anti-fog coating in a high temperature and high humidity environment.
[0038] As a preferred solution, the cross-linking monomer is styrene.
[0039] As a preferred solution, the cross-linking auxiliary agent is a combination of tetramethylol glycoluril and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.
[0040] As a preferred solution, the mass ratio of the tetrakishydroxymethyl glycoluril to 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione is (3-4):(1.5-2).
[0041] As a preferred solution, the mass ratio of the tetrakishydroxymethyl glycoluril to 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione is (3.4-3.8):(1.6-1.8).
[0042] In this application, by adopting the above-mentioned specific cross-linking monomer, cross-linking aid and hyperbranched polyurethane acrylate resin and other resin materials, the anti-fog, corrosion resistance and mechanical properties of the prepared coating can be effectively improved. The cross-linking aid combination of tetramethylol glycoluril and 1,3-bis(oxiranylmethyl)-5-(2-propylene)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione added in this application can effectively serve as the active molecular chain site in the benzene propylene cross-linking reaction in the system, thereby enhancing the entanglement degree of the cross-linking site inside the system after the coating is cured, achieving high molecular chain chimera with hyperbranched polyurethane acrylate, thereby greatly enhancing the interaction force between the three-dimensional molecular chain network inside the coating system, thereby enhancing the intermolecular tightness, improving the enhancement effect of the moisture control powder and filler particles on the internal space steric hindrance, and finally greatly reducing the migration efficiency of water molecules and free active groups in the coating, improving the penetration resistance and path length of water molecules or active molecules with water molecules as carriers, and maintaining good anti-fog and aging corrosion effects.
[0043] On the other hand, the added tetramethylol glycoluril and hyperbranched polyurethane acrylate contain multi-active group structures, which can serve as excellent carriers of moisture control powders and modified fillers in the formation process of the coating system, especially for the hydrogen bonding and intermolecular attraction on the surface of modified composite particles and some hygroscopic powders, which can effectively enhance the interaction between the particles and the system resin in the coating, and play a good connection and fixing effect, thereby greatly reducing the pore size of the micropores formed by the powder particles and filler particles in the coating system, thereby avoiding the negative impact of excessive pore size on mechanical properties and anti-fog properties, and obtaining excellent anti-fog and aging and corrosion resistance auxiliary enhancement effects.
[0044] As a preferred solution, the foaming agent is azodicarbonamide or azobisisobutyronitrile.
[0045] As a preferred solution, the antibacterial agent is chitosan.
[0046] As a preferred solution, the UV-resistant agent is at least one of glycidyloxypropyl cage-type polysilsesquioxane, 2-(2′-hydroxy-3′,5′-di-tert-butylphenyl)-5-chlorobenzotriazole, and 2-(4′-tert-butylphenyl)-4,6-diphenyl-1,3,5-triazine.
[0047] As a preferred solution, the UV-resistant agent is glycidyloxypropyl cage-type polysilsesquioxane.
[0048] As a preferred embodiment, the initiator is at least one of 2-hydroxy-2-methyl-1-phenylpropan-1-one, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone or 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0049] As a preferred solution, the initiator is 2-hydroxy-2-methyl-1-phenylpropan-1-one.
[0050] As a preferred solution, the catalyst is any one of acid catalysts.
[0051] As a preferred solution, the catalyst is acetic acid.
[0052] As a preferred solution, the auxiliary agent at least includes a plasticizer, a surfactant and a coupling agent.
[0053] As a preferred solution, the mass ratio of the plasticizer, surfactant and coupling agent is (5-10): (1-3): (2-4).
[0054] As a preferred solution, the mass ratio of the plasticizer, surfactant and coupling agent is (6-8): (1.5-2): (3-3.5).
[0055] As a preferred solution, the plasticizer is at least one of white oil, epoxidized soybean oil or naphthenic oil.
[0056] As a preferred solution, the plasticizer is white oil.
[0057] As a preferred solution, the surfactant is at least one of sodium fatty acid, lauryl alcohol polyoxyethylene ether or cetearyl alcohol polyoxyethylene ether.
[0058] As a preferred solution, the surfactant is sodium fatty acid.
[0059] As a preferred solution, the coupling agent is 3-aminopropyltrimethoxysilane or γ-glycidyloxypropyltrimethoxysilane.
[0060] As a preferred solution, the coupling agent is 3-aminopropyltrimethoxysilane.
[0061] The second aspect of the present application provides a method for preparing the above-mentioned anti-fog coating for a vehicle-mounted camera, which specifically comprises the following steps: S1: mixing the resin material and the methyl vinyl silicone rubber in a mixing container, heating to 50-60°C, stirring and mixing at 200-400rpm for 40-60min until uniform, to obtain a mixture; S2: adding the mixture to a reaction container, adding microcapsules, moisture control powders and functional fillers, heating to 65-70°C, stirring and mixing at 500-600rpm for 40-60min until uniform. S3: then add the cross-linking monomer, cross-linking auxiliary agent, foaming agent, antibacterial agent, UV resistant agent, initiator, catalyst and auxiliary agent in sequence, continue to stir at 65~70℃, 500~600rpm for 10~15min after each addition to ensure uniform mixing, after all the ingredients are added, move them into the vacuum degassing device, degassing at 70~75℃ for 20~30min, and obtain a mixed coating; S4: dip-coat the mixed coating on the desired surface, irradiate with ultraviolet light at a power density of 80~120 W / cm² until the coating is completely cured.
[0062] The beneficial effects of this application are: 1. The anti-fog coating for a vehicle-mounted camera provided in the present application not only has excellent anti-fog performance, but also ensures its good aging resistance, corrosion resistance and mechanical properties, and can ensure its performance stability in a long-term high temperature and high humidity environment, avoiding the moisture absorption and saturation phenomenon of the existing anti-fog coating in a long-term high temperature and high humidity environment, so that it ensures the anti-condensation effect under normal use, realizes the dynamic balance of the ambient humidity in the vehicle-mounted camera, and plays a role in protecting optical and electronic components within a suitable humidity range, and has a very excellent application prospect.
[0063] 2. The present application provides an anti-fog coating for a vehicle-mounted camera, in which the added modified composite particles are coordinated and embedded with titanium dioxide particles by adsorbing the surface of the framework particles, thereby forming a composite structure in which multiple titanium dioxide particles cover the framework particles. The existence of this structure can firstly utilize the multiple active groups of the surface titanium dioxide to form good hydrogen bonds or intermolecular forces with the organic resin in the coating system to fix it, thereby achieving a good dispersion effect, reducing the pore size of the particle pores, providing a good support effect for the mechanical properties of the coating system, and ensuring a good working environment system for other functions.
[0064] 3. The anti-fog coating for a vehicle-mounted camera provided in the present application has modified composite particles added thereto, and the framework particles located in the center of the composite structure can desorb water molecules in a high temperature environment through the amino group and its own adsorption characteristics, thereby maintaining a low moisture absorption level in a high temperature and high humidity environment, and when the ambient temperature drops below the critical temperature, it can re-achieve excellent water molecule adsorption, thereby avoiding the moisture saturation phenomenon of the existing anti-fog coating in a high temperature and high humidity environment.
[0065] 4. The anti-fog coating for vehicle-mounted cameras provided in the present application contains a multi-active group structure of tetrahydroxymethyl glycoluril and hyperbranched polyurethane acrylate, which can serve as an excellent carrier for moisture control powder and modified filler in the formation process of the coating system, especially for the hydrogen bonding effect and intermolecular attraction on the surface of modified composite particles and some hygroscopic powders, which can effectively enhance the interaction force between the particles and the system resin in the coating, and play a good connection and fixing effect, thereby greatly reducing the pore size of the micropores formed by the powder particles and filler particles in the coating system, thereby avoiding the negative impact of excessive pore size on mechanical properties and anti-fog performance, and obtaining excellent anti-fog and aging and corrosion resistance auxiliary enhancement effects. DETAILED DESCRIPTION
[0066] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0067] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art. Example 1
[0068] Embodiment 1 The first aspect provides an anti-fog coating for a vehicle-mounted camera. The raw materials, in parts by mass, are: 50 parts of resin material, 15 parts of methyl vinyl silicone rubber, 13.5 parts of microcapsules, 24.8 parts of moisture control powder, 23.2 parts of functional fillers, 6.8 parts of cross-linking monomers, 5 parts of cross-linking aids, 6.5 parts of foaming agents, 3.2 parts of antibacterial agents, 3.8 parts of UV resistant agents, 1.8 parts of initiators, 3.6 parts of catalysts, and 12.4 parts of additives.
[0069] The resin material is a composition of hyperbranched polyurethane acrylate resin and polyethylene glycol diacrylate resin, and the mass ratio of the two is 4: 1. The weight average molecular weight of the hyperbranched polyurethane acrylate resin is 12000Da, and the corresponding molecular weight product is purchased from Dongguan Jingshang New Material Development Co., Ltd.
[0070] The weight average molecular weight of polyethylene glycol diacrylate resin is 800 Da, and it is purchased from Zhongshan Dixin Chemical Co., Ltd.
[0071] The viscosity of the methyl vinyl silicone rubber is 1200 mPa·s at 25° C. and it is purchased from Wacker Chemicals as the ELASTOSIL® M 3030 grade product.
[0072] The microcapsules are paraffin-urea-formaldehyde resin microcapsules, which are F0 grade products purchased from Shanghai Yuyu New Material Technology Co., Ltd.
[0073] The moisture control powder is a composition of nano-alumina, nano-silica gel, calcium chloride, magnesium chloride and calcium nitrate, with a mass ratio of 7.5:4:3.5:1.5:1.
[0074] The average particle size of nano-alumina is 18nm; the specific surface area of nano-silica gel is 484m 2 / g, purchased from Shanghai McLean Biochemical Technology Co., Ltd. sold the corresponding specific surface area model products; the average particle size of calcium chloride is 15μm, the average particle size of magnesium chloride is 12.5μm, the average particle size of calcium nitrate is 20μm, calcium chloride, magnesium chloride and calcium nitrate are purchased from Shanghai McLean Biochemical Technology Co., Ltd. sold the corresponding particle size products.
[0075] The functional filler is a composition of calcium carbonate and modified composite particles, and the mass ratio of the two is 3.2:2.
[0076] The average particle size of calcium carbonate is 300 nm, and the corresponding particle size model product is purchased from Shandong Tianan New Materials Co., Ltd.
[0077] The preparation method of modified composite particles comprises the following steps, calculated by mass: S1: adding 5.4 parts of aluminum chloride and 0.75 parts of titanium dioxide to 200 parts of DMF, ultrasonically dispersing at 240W for 25 minutes, then adding 0.6 parts of citric acid, 2.1 parts of succinic anhydride and 0.22 parts of methacryloxysilane coupling agent, heating to 65°C and keeping warm for 2.5 hours, centrifugally filtering, washing and drying to obtain pretreated mixed particles; S2: adding 3.2 parts of pretreated mixed particles to a mixed solvent of 220 parts of DMF and methanol (the mass ratio of DMF to methanol is 4:1), adding 2 .2 parts of p-aminobenzoic acid and 0.6 parts of terephthalic acid are stirred in a sealed reactor at 125°C and 200rpm for 18 hours. After the reaction is completed, it is naturally cooled to room temperature, centrifuged, washed with DMF and methanol for 3 times in a cycle, and vacuum dried to obtain pre-product particles; S3: 3.8 parts of pre-product particles and 10 parts of ethanol are added to 120 parts of deionized water, the pH is adjusted to 10.2 with ammonia water, 0.55 parts of tetraethyl orthosilicate and 0.08 parts of triethanolamine are added, the temperature is raised to 64°C and kept warm for 1.2 hours. After completion, the deionized water is washed for 3 times in a cycle, and vacuum dried to obtain.
[0078] The average particle size of titanium dioxide is 5 nm; the average particle size of the modified composite particles is 517 nm.
[0079] The cross-linking monomer is styrene; the cross-linking auxiliary agent is a composition of tetramethylol glycoluril and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and the mass ratio of the two is 3.5:1.8.
[0080] The foaming agent is azodicarbonamide; the antibacterial agent is chitosan, which is a food-grade antibacterial chitosan product purchased from Zhejiang Yicun Biotechnology Co., Ltd.
[0081] The UV-resistant agent is glycidyl ether oxypropyl cage-type polysilsesquioxane, which is a high-purity GR product purchased from Xi'an Qiyue Biotechnology Co., Ltd.
[0082] The initiator is 2-hydroxy-2-methyl-1-phenylpropan-1-one; and the catalyst is acetic acid.
[0083] The additives are plasticizer, surfactant and coupling agent, and the mass ratio of the three is 6.5:2:3.
[0084] The plasticizer is white oil #5; the surfactant is sodium fatty acid; and the coupling agent is 3-aminopropyltrimethoxysilane.
[0085] The second aspect of the present embodiment provides a method for preparing the above-mentioned anti-fog coating for vehicle-mounted cameras, which specifically includes the following steps: S1: mixing the resin material and methyl vinyl silicone rubber in a mixing container, heating to 60°C, stirring and mixing at 300rpm for 50min until uniform, to obtain a mixture; S2: adding the mixture to a reaction container, adding microcapsules, moisture control powder and functional fillers, heating to 70°C, stirring and mixing at 550rpm for 45min until uniform; S3: then adding a cross-linking monomer, a cross-linking auxiliary agent, a foaming agent, an antibacterial agent, an ultraviolet resistant agent, an initiator, a catalyst and an auxiliary agent in sequence, and continuing to stir at 70°C and 550rpm for 12min after each addition to ensure uniform mixing. After all the ingredients are added, they are transferred to a vacuum degassing device, degassed at 75°C for 25min to obtain a mixed coating; S4: dip-coating the mixed coating on the desired surface, and irradiating it with ultraviolet light at a power density of 100 W / cm² until the coating is completely cured. Example 2
[0086] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the anti-fog coating for vehicle-mounted cameras comprises, by weight, 55 parts of resin, 12 parts of methyl vinyl silicone rubber, 12.2 parts of microcapsules, 28 parts of moisture control powders, 18 parts of functional fillers, 8 parts of cross-linking monomers, 5 parts of cross-linking aids, 6.5 parts of foaming agents, 3.2 parts of antibacterial agents, 3.8 parts of UV-resistant agents, 1.8 parts of initiators, 3.6 parts of catalysts, and 12.4 parts of aids.
[0087] The resin material is a composition of hyperbranched polyurethane acrylate resin and polyethylene glycol diacrylate resin, and the mass ratio of the two is 4.5:0.9.
[0088] The moisture control powder is a composition of nano-alumina, nano-silica gel, calcium chloride, magnesium chloride and calcium nitrate, with a mass ratio of 6:4.5:3:1:1.5.
[0089] The functional filler is a composition of calcium carbonate and modified composite particles, and the mass ratio of the two is 4:1.5.
[0090] The additives are plasticizer, surfactant and coupling agent, and the mass ratio of the three is 8:1.5:3.5. Example 3
[0091] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the anti-fog coating for vehicle-mounted cameras comprises, by weight, 46 parts of resin, 18 parts of methyl vinyl silicone rubber, 14 parts of microcapsules, 22 parts of moisture control powders, 25 parts of functional fillers, 5 parts of cross-linking monomers, 5 parts of cross-linking aids, 6.5 parts of foaming agents, 3.2 parts of antibacterial agents, 3.8 parts of UV resistant agents, 1.8 parts of initiators, 3.6 parts of catalysts, and 12.4 parts of aids.
[0092] The resin material is a composition of hyperbranched polyurethane acrylate resin and polyethylene glycol diacrylate resin, and the mass ratio of the two is 4:1.3.
[0093] The moisture control powder is a composition of nano-alumina, nano-silica gel, calcium chloride, magnesium chloride and calcium nitrate, with a mass ratio of 8:4:3.5:2:2.
[0094] The functional filler is a composition of calcium carbonate and modified composite particles, and the mass ratio of the two is 3:2.2.
[0095] The additives are plasticizer, surfactant and coupling agent, and the mass ratio of the three is 5:2.5:2.
[0096] Comparative Example 1 The specific implementation manner of this comparative example is basically the same as that of Example 1, except that: the anti-fog coating for vehicle-mounted cameras, in parts by mass, comprises the following raw materials: 65 parts of resin material, 8 parts of methyl vinyl silicone rubber, 8.8 parts of microcapsules, 28.6 parts of moisture control powders, 15.2 parts of functional fillers, 2.5 parts of cross-linking monomers, 5 parts of cross-linking aids, 6.5 parts of foaming agents, 3.2 parts of antibacterial agents, 3.8 parts of UV-resistant agents, 1.8 parts of initiators, 3.6 parts of catalysts, and 12.4 parts of aids.
[0097] Comparative Example 2 The specific implementation manner of this comparative example is basically the same as that of Example 1, except that: the anti-fog coating for vehicle-mounted cameras, in parts by mass, comprises the following raw materials: 40 parts of resin material, 20 parts of methyl vinyl silicone rubber, 5.5 parts of microcapsules, 15.2 parts of moisture control powders, 35.5 parts of functional fillers, 6.8 parts of cross-linking monomers, 5 parts of cross-linking aids, 6.5 parts of foaming agents, 3.2 parts of antibacterial agents, 3.8 parts of UV resistant agents, 1.8 parts of initiators, 3.6 parts of catalysts, and 12.4 parts of aids.
[0098] Comparative Example 3 The specific implementation of this comparative example is basically the same as that of Example 1, except that the crosslinking monomer is a composition of p-methylstyrene and 2-ethylhexyl acrylate, and the mass ratio of the two is 0.8:2.
[0099] Comparative Example 4 The specific implementation of this comparative example is basically the same as that of Example 1, except that the crosslinking aid is a composition of tetrakishydroxymethyl glycoluril and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and the mass ratio of the two is 4.5:0.4.
[0100] Comparative Example 5 The specific implementation of this comparative example is basically the same as that of Example 1, except that the crosslinking aid is a composition of tetrakishydroxymethyl glycoluril and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and the mass ratio of the two is 1:1.8.
[0101] Comparative Example 6 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified composite particles comprises the following steps, calculated by mass: S1: adding 8.5 parts of aluminum chloride and 0.35 parts of titanium dioxide to 200 parts of DMF, ultrasonically dispersing at 240W for 25 minutes, then adding 0.4 parts of citric acid, 1.1 parts of succinic anhydride and 0.1 parts of methacryloxysilane coupling agent, heating to 65°C and keeping warm for 2.5 hours, centrifugally filtering, washing and drying to obtain pretreated mixed particles; S2: adding 5.5 parts of the pretreated mixed particles to a mixed solvent of 220 parts of DMF and methanol (DMF and methanol) The mass ratio of alcohol is 4:1), 2.2 parts of p-aminobenzoic acid and 0.6 parts of terephthalic acid are added, and the reaction is stirred in a sealed reactor at 125°C and 200rpm for 18 hours. After the reaction is completed, it is naturally cooled to room temperature, centrifuged, washed with DMF and methanol in a cycle for 3 times in sequence, and vacuum dried to obtain pre-product particles; S3: 3.8 parts of pre-product particles and 10 parts of ethanol are added to 120 parts of deionized water, the pH is adjusted to 10.2 with ammonia water, 0.55 parts of tetraethyl orthosilicate and 0.08 parts of triethanolamine are added, the temperature is raised to 64°C and kept warm for 1.2 hours, and after completion, the deionized water is circulated and washed 3 times, and vacuum dried to obtain.
[0102] The average particle size of the modified composite particles was 384 nm.
[0103] Comparative Example 7 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified composite particles comprises the following steps, calculated by mass: S1: adding 7.5 parts of aluminum chloride and 0.75 parts of titanium dioxide to 200 parts of DMF, ultrasonically dispersing at 240W for 25 minutes, then adding 0.6 parts of citric acid, 2.1 parts of succinic anhydride and 0.22 parts of methacryloxysilane coupling agent, heating to 65°C and keeping warm for 2.5 hours, centrifugally filtering, washing and drying to obtain pretreated mixed particles; S2: adding 1.5 parts of the pretreated mixed particles to a mixed solvent of 220 parts of DMF and methanol (DMF and The mass ratio of methanol is 4:1), 4.5 parts of p-aminobenzoic acid and 2.5 parts of terephthalic acid are added, and the reaction is stirred in a sealed reactor at 125°C and 200rpm for 18 hours. After the reaction is completed, it is naturally cooled to room temperature, centrifuged, washed with DMF and methanol in a cycle for 3 times in sequence, and vacuum dried to obtain pre-product particles; S3: 3.8 parts of pre-product particles and 10 parts of ethanol are added to 120 parts of deionized water, the pH is adjusted to 10.2 with ammonia water, 1.8 parts of tetraethyl orthosilicate and 0.22 parts of triethanolamine are added, the temperature is raised to 64°C and kept warm for 1.2 hours, and after completion, the deionized water is circulated and washed 3 times, and vacuum dried to obtain.
[0104] The average particle size of the modified composite particles is 675 nm.
[0105] Comparative Example 8 The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of titanium dioxide is 35 nm; and the average particle size of the modified composite particles is 722 nm.
[0106] Performance Evaluation Adhesion performance test: The product was applied to an aluminum plate. After curing, the overall adhesion strength of the coating was tested using a tensile peel tester. The test value was the average of 10 tests and recorded in Table 1.
[0107] Moisture absorption test: Apply the product to a metal plate, and after curing, place it in an environment of 25°C and 96±2% humidity for 24 hours, test its weight, and calculate its overall moisture absorption before and after the test. The test value is the average of 10 tests and recorded in Table 1.
[0108] High temperature and high humidity resistance test: Apply the product to the metal plate, and after curing, place it in a constant temperature and humidity chamber at 85±3℃ and 75±2% relative humidity for 1000h. After completion, observe the surface condition. If there is any peeling, cracking or yellowing of the coating, it is considered unqualified, otherwise it is qualified. 50 groups of samples are tested in each group, and the qualified rate of each group is calculated and recorded in Table 1.
[0109] Salt corrosion resistance test: The coatings prepared in the examples and comparative examples were subjected to a 5wt% NaCl corrosion resistance test. A coating sample with a thickness of 1.5 mm was immersed in a 5wt% NaCl solution for 400 h. The coating was then taken out and observed for cracking, blistering, hydrolysis, and corrosion oxidation. If any, it was qualified, otherwise it was unqualified. 50 groups of samples were tested in each group, and the qualified rate was recorded in Table 1.
[0110] Table 1 Performance test results Example Adhesion strength (MPa) <![CDATA[Moisture absorption (g / m 2 ·24h)]]> High temperature and high humidity resistance qualified rate (%) Salt spray corrosion resistance qualified rate (%) Example 1 1.41 69.9 98 98 Example 2 1.36 67.4 96 94 Example 3 1.39 66.8 98 96 Comparative Example 1 1.17 52.3 90 90 Comparative Example 2 1.09 54.4 92 92 Comparative Example 3 1.11 51.4 88 86 Comparative Example 4 1.24 47.1 86 80 Comparative Example 5 1.29 48.2 90 82 Comparative Example 6 1.25 49.4 82 78 Comparative Example 7 1.11 47.9 80 76 Comparative Example 8 1.22 46.8 84 80 It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that examples 1 to 3 of the present application have obvious advantages over comparative examples 1 to 8 in terms of bonding performance, anti-fog performance, high temperature resistance and corrosion resistance. This is mainly due to the combined effect of the specified resin material, specified cross-linking system scheme and modified composite particles and other matching schemes specified in the present application. Comparative examples 1 to 8 did not adopt the technical scheme specified in the present application, resulting in obvious disadvantages in the above performance tests. This further proves the necessity of the technical scheme specified in the present application for the technical effect of the present application and solving technical problems.
Claims
1. An anti-fog coating for a vehicle-mounted camera, characterized in that: The raw materials are as follows: 45-60 parts of resin, 10-20 parts of methyl vinyl silicone rubber, 10-15 parts of microcapsules, 20-35 parts of moisture control powders, 15-25 parts of functional fillers, 5-10 parts of crosslinking monomers, 3-5 parts of crosslinking aids, 5-8 parts of foaming agents, 3-4 parts of antibacterial agents, 2-4 parts of UV resistant agents, 1-2 parts of initiators, 2-4 parts of catalysts, and 8-15 parts of additives. The resin material is a composition of a hyperbranched polyurethane acrylate resin and a polyethylene glycol diacrylate resin; the mass ratio of the hyperbranched polyurethane acrylate resin to the polyethylene glycol diacrylate resin is (4-4.5): (0.9-1.3); The weight average molecular weight of the hyperbranched polyurethane acrylate resin is 10000-15000Da; The weight average molecular weight of the polyethylene glycol diacrylate resin is 600-1000Da; The viscosity of the methyl vinyl silicone rubber is 1000-1500 mPa·s at 25°C; The microcapsule is paraffin-urea-formaldehyde resin microcapsule; The moisture control powder is a composition of nano-alumina, nano-silica gel, calcium chloride, magnesium chloride and calcium nitrate; the mass ratio of the nano-alumina, nano-silica gel, calcium chloride, magnesium chloride and calcium nitrate is (6-8): (4-4.5): (3-3.5): (1-2): (1-2); The average particle size of the nano-alumina is 10-20 nm; The functional filler is a composition of calcium carbonate and modified composite particles; the mass ratio of the calcium carbonate and the modified composite particles is (3-4): (1.5-2.2); Preparation method of the modified composite particles The following steps are involved: S1: Aluminum chloride and titanium dioxide are added to DMF, and ultrasonically dispersed at 200-250W for 20-30min, and then citric acid, succinic anhydride and methacryloxysilane coupling agent are added, and the temperature is raised to 60-70°C and kept for 2-3h, and then centrifuged and filtered, and the pretreated mixed particles are obtained after washing and drying; S2: Add the pretreated mixed particles to a mixed solvent of DMF and methanol, add p-aminobenzoic acid and terephthalic acid, and stir in a sealed reactor at 120-140°C and 200-240 rpm for 16-20 hours. After the reaction is completed, naturally cool to room temperature, centrifuge, wash with DMF and methanol in a cycle for 2-3 times, and vacuum dry to obtain pre-product particles; S3: Add the pre-product particles and ethanol to deionized water, adjust the pH to 10-10.5 with ammonia water, add tetraethyl orthosilicate and triethanolamine, heat to 60-65°C and keep warm for 1-1.5 hours, wash with deionized water in a cycle for 2-3 times, and vacuum dry to obtain; The mass ratio of the aluminum chloride, titanium dioxide, citric acid, succinic anhydride and methacryloxysilane coupling agent is (5-5.5): (0.6-1): (0.5-0.7): (2-2.2): (0.2-0.3); The mass ratio of aminobenzoic acid to terephthalic acid in the pretreated mixed particles is (3-3.2): (2.1-2.4): (0.5-0.8); The average particle size of the modified composite particles is 420-550 nm.
2. The anti-fog coating for a vehicle-mounted camera according to claim 1, characterized in that: The mass ratio of the resin material, methyl vinyl silicone rubber and cross-linking monomer is (46-55): (12-18): (5-8).
3. The anti-fog coating for a vehicle-mounted camera according to claim 2, characterized in that: The mass ratio of the microcapsule, the moisture control powder and the functional filler is (12-14): (22-28): (18-25).
4. The anti-fog coating for a vehicle-mounted camera according to claim 3, characterized in that: The specific surface area of the nano silica gel is 400-500m 2 / g.
5. The anti-fog coating for a vehicle-mounted camera according to claim 4, characterized in that: The mass ratio of the pre-product particles, tetraethyl orthosilicate and triethanolamine is (3.6-4): (0.4-0.6): (0.05-0.1).
6. The anti-fog coating for a vehicle-mounted camera according to claim 5, characterized in that: The average particle size of the titanium dioxide is 5-10 nm.
7. The anti-fog coating for a vehicle-mounted camera according to claim 6, characterized in that: The cross-linking monomer is styrene.
8. The anti-fog coating for a vehicle-mounted camera according to claim 7, characterized in that: The cross-linking auxiliary agent is a composition of tetrakishydroxymethyl glycoluril and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione; the mass ratio of the tetrakishydroxymethyl glycoluril and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione is (3~4):(1.5~2).
9. The anti-fog coating for a vehicle-mounted camera according to claim 8, characterized in that: The auxiliary agent at least includes a plasticizer, a surfactant and a coupling agent; the mass ratio of the plasticizer, the surfactant and the coupling agent is (5-10): (1-3): (2-4).
10. A method for preparing an anti-fog coating for a vehicle-mounted camera according to any one of claims 1 to 9, characterized in that: The specific steps include: S1: Mix the resin material and methyl vinyl silicone rubber in a mixing container, heat it to 50-60°C, stir and mix at 200-400rpm for 40-60min until uniform, and obtain a mixture; S2: Add the mixture to a reaction container, add microcapsules, moisture control powder and functional fillers, heat it to 65-70°C, stir and mix at 500-600rpm for 40-60min until uniform; S3: Then add cross-linking monomer, cross-linking auxiliary agent, foaming agent, antibacterial agent, UV resistant agent, initiator, catalyst and auxiliary agent in sequence, continue to stir at 65-70°C and 500-600rpm for 10-15min after each addition to ensure uniform mixing, and after all ingredients are added, move them into a vacuum degassing device, degassing at 70-75°C for 20-30min, and obtain a mixed coating; S4: Dip-coat the mixed coating on the desired surface and irradiate it with UV light at a power density of 80~120 W / cm² until the coating is completely cured.
Citation Information
Patent Citations
High-efficiency composite visible-light catalyst with core-shell structure, and preparation method and application thereof
CN110152741A
Anti-shedding waterproof coating for building exterior walls and preparation method thereof
CN112608649A
Preparation method and application method of super-hydrophobic coating
CN112920674A
Preparation method of MOFs (Metal-Organic Frameworks) derived sub-nano active site photocatalyst
CN116571261A
Humidifying material suitable for high-temperature environment of metal vehicle-mounted camera and vehicle lamp
CN116855067A
Cited By
Reflective heat-insulation rock slice real stone paint as well as preparation method and application thereof
CN119842276A
Reflective heat-insulating rock slice real stone paint and preparation method and application thereof
CN119842276B